Telaah Yuridis Gharar dalam Fatwa DSN-MUI dan Relevansinya dengan Kompilasi Hukum Ekonomi Syariah (KHES) - Susandi, Adi; Fauzan Januri; Sofian Al-Hakim (TAFAQQUH, 2025)
This study provides a normative-juridical review of the concept of gharar in five fatwas issued by Indonesia's National Sharia Council (DSN-MUI) that directly relate to muamalah contracts, and examines their relevance to the Compilation of Sharia Economic Law (KHES). Using content analysis of primary legal documents, the study finds that: (1) DSN-MUI formulates gharar explicitly and operationally within specific contract types; (2) KHES contains substantive principles relevant to the prohibition of gharar but does not mention the term explicitly; and (3) harmonization between the two is highly feasible at the level of principles, but requires structural reform at the normative formulation level. The study recommends amendments to KHES, formalization of fatwas as jurisprudence, and strengthening judges' capacity in applied fiqh muamalah as concrete steps toward harmonization.